Efficient production of cordycepin by engineered Yarrowia lipolytica from agro-industrial residues. (June 2023) - Duan, Xi-Yu; Liu, Hu-Hu; Song, Li-Ping; Wang, Chong; Yang, Hui; Lu, Xiang-Yang; Ji, Xiao-Jun; Tian, Yun
Graphical abstract: Highlights: Co-overexpression of GLK1 and PGM1 significantly promoted cordycepin accumulation. Molasses, DHP, and waste yeast as alternate enhanced cordycepin production. High C/N molar ratio and weak acidic were more conducive to producing cordycepin. The cordycepin productivity in the optimized medium was increased by 28.81%. Using agro-industrial residues can reduce the cost of cordycepin production. Abstract: Cordycepin, a nucleoside compound with a variety of biological activities, has been extensively applied in the nutraceutical and pharmaceutical industries. The advancement of microbial cell factories using agro-industrial residues provides a sustainable pathway for cordycepin biosynthesis. Herein, the cordycepin production was enhanced by the modification of glycolysis and pentose phosphate pathway in engineered Yarrowia lipolytica . Then, cordycepin production based on economical and renewable substrates (sugarcane molasses, waste spent yeast, and diammonium hydrogen phosphate) was analyzed. Furthermore, the effects of C/N molar ratio and initial pH on cordycepin production were evaluated. Results indicated that the maximum cordycepin productivity of 656.27 mg/L/d (72 h) and cordycepin titer was 2286.04 mg/L (120 h) by engineered Y. lipolytica in the optimized medium, respectively. The cordycepin productivity in the optimized medium was increased by 28.81% compared with the original medium. This research establishes a promising way for efficient cordycepin production from agro-industrial residues.